Improving Hippocampal Memory Through the Experience of a Rich Minecraft Environment - Clemenson, Gregory D.; Henningfield, Caden M.; Stark, Craig E. L. (Frontiers in Behavioral Neuroscience, 2019)
It is well known that the brain changes in response to the surrounding environment. The hippocampus has been shown to be particularly susceptible to environmental enrichment, with effects ranging from the generation of new hippocampal neurons and synapses to an increased expression of neurotrophic factors. While many of these changes in the hippocampus are well documented in animals, our understanding of how environmental enrichment can apply to humans is more ambiguous. In animals, spatial exploration has been shown to be a clear way to elicit the effects of environmental enrichment and considering the role of the hippocampus in spatial navigation, which has been shown in both animal models and humans, it suggests a viable avenue for translation of environmental enrichment to humans. Here we test the hypothesis that the spatial exploration of a virtual video game environment, can impact the hippocampus and lead to an improvement in hippocampal-dependent memory. Using the video game Minecraft, we tested four groups of participants, each playing on custom servers and focusing on different aspects of Minecraft to test the effects of both building and exploration over the course of two weeks. We found an improvement in hippocampus-associated memory from pre-test to post-test and that the degree of improvement was tied to both the amount of exploration of the Minecraft world and the complexity of the structures built within Minecraft. Thus, the amount of enrichment participants engaged in while playing Minecraft was directly correlated with improvements in hippocampal-dependent memory outside of the game.